A IMPACT OF HYGROPHILA AURICULATA-GREEN MOSQUITOCIDAL ACTIVITY AGAINST MALARIA VECTOR, ANOPHELES STEPHENSI (DIPTERA: CULICIDAE): HYGROPHILA AURICULATA-GREEN MOSQUITOCIDAL ACTIVITY AGAINST MALARIAL VECTOR - BALU SUBASH; PERIYASAMY VIJAYAN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Mosquitoes are insect vectors responsible for the transmission of parasitic and viral infections to millions of people worldwide, with substantial morbidity and mortality. Insecticides of botanical origin may serve as suitable alternative bio-control techniques in the future. Methods: The egg hatchability, growth regulatory, longevity, fecundity, and larvicidal activity of crude methanol leaf extract of Hygrophila auriculata were assayed for their toxicity tested against malarial vector mosquito, Anopheles stephensi. Results: The eggs, larvae, larvae/pupae, and cumulative mortality were observed hatching rates for 100 ppm, 0–18 h (18 h exposed) at 24, 48, and 72 h, respectively, and mortality was 33.4, 44.6, 17.9, and 95.9% methanolic extract treatment, with the lethal concentration 50 (LC50)/LC90 values were 35.420 28/75.600 ppm. Effect of methanolic extract was larval, pupal, and adult duration and water extracts of caused longest delayed development from 16.6 days larvae, 7.5 days for pupae and longevity of adult female greatly reduced from 25.9 days and fecundity also reduced from 68.0 at 150 ppm. The larvicidal activity of methanol extract was decreased at 48 h as for instars larvae 63.44/271.95 ppm (I), 57.55/272.48 ppm (II); 62.49/301.22 ppm (III); 67.69/330.48 ppm (IV), and 76.99/343.82 ppm (pupae), respectively. Conclusion: These results suggest that the methanol leaf extract has the potential to be used as an ideal eco-friendly approach for the control of mosquito vector. Therefore, this study provides on the mosquito eggs, larvae, and pupae activities of these plant methanol extract against A. stephensi.